1998
DOI: 10.2337/diacare.21.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen T235 and ACE Insertion/Deletion Polymorphisms Associated With Albuminuria in Chinese Type 2 Diabetic Patients

Abstract: The high frequencies of the TT genotype and T allele in Chinese populations may contribute to the high prevalence of albuminuria in patients with type 2 diabetes. The possibility of synergism between the AGT TT genotype and the ACE D allele should also be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
27
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 0 publications
7
27
5
Order By: Relevance
“…The frequency of the ACE DD genotype in our control Taiwan Chinese population was 18%, which is higher than that Vol 45 No 6 reported in Hong Kong Chinese (13%), but lower than in both Turkish (61.2%) and Caucasian populations (24.8%). [30][31][32] The frequency of the D allele in our control Taiwan Chinese population was 44%, which is higher than that reported in Hong Kong Chinese (37.2%), but lower than that in both Turkish (61.2%) and Caucasian populations (54%). [30][31][32] The discrepancy in the distribution of ACE gene I/D polymorphism between these studies may be due to ethnic differences.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The frequency of the ACE DD genotype in our control Taiwan Chinese population was 18%, which is higher than that Vol 45 No 6 reported in Hong Kong Chinese (13%), but lower than in both Turkish (61.2%) and Caucasian populations (24.8%). [30][31][32] The frequency of the D allele in our control Taiwan Chinese population was 44%, which is higher than that reported in Hong Kong Chinese (37.2%), but lower than that in both Turkish (61.2%) and Caucasian populations (54%). [30][31][32] The discrepancy in the distribution of ACE gene I/D polymorphism between these studies may be due to ethnic differences.…”
Section: Discussioncontrasting
confidence: 42%
“…[30][31][32] The frequency of the D allele in our control Taiwan Chinese population was 44%, which is higher than that reported in Hong Kong Chinese (37.2%), but lower than that in both Turkish (61.2%) and Caucasian populations (54%). [30][31][32] The discrepancy in the distribution of ACE gene I/D polymorphism between these studies may be due to ethnic differences. Thus, the findings in a Turkish population can not be extrapolated to a Taiwanese population.…”
Section: Discussioncontrasting
confidence: 42%
“…This change in the protein seems to be reflected in AGT plasma concentrations where AA homozygous individuals present with an 11% higher concentration than that of GG homozygous individuals (Sethi et al, 2003). Our findings are in agreement with prior studies that have found an association between this polymorphism and DM2 (Young et al, 1998;Mehri et al, 2010). Additionally, meta-analyses have also reported associations between the A allele of the polymorphism and the risk of cardiovascular diseases Pan, 2012, 2013;Liang et al, 2013a,b;Li et al, 2013;Chen et al, 2014), renal failure (Zhou et al, 2013b), pre-eclampsia (Lin et al, 2012), and breast cancer (Xi et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…The DD genotype or D allele of this polymorphism was shown to be associated with elevated circulating and tissue ACE activity (4) as well as increased risk of hypertension (5) and diabetic renal (6) and cardiovascular complications (7). However, these results remained inconsistent in both Caucasian (8 -11) and non-Caucasian populations, including Chinese (12,13). These discrepancies might be due to ethnicity, study design, patient selection criteria, and small sample size.…”
mentioning
confidence: 50%